Sniff Bounces Back - "Ross, Tony" (Hodder and Childrens Books: London, 1999)
Sniff is a wild and woolly dog who adopted the family he lives with. For Ben Moore, already plagued by his screamy little sister Sal, it's a tough job keeping out of trouble once Sniff starts muscling in.
Keywords: Dogs Juvenile fiction